COMPARISON OF COMPRESSIBILTY CHARACTERISTICS OF BUSAN LEACHED AND UNLEACHED CLAYS - Y. T. Kim; T. H. Do (International Association of Lowland Technology, 2009)
It is well known that the settlement of soft deposit increases with leaching process due to bond weakness of soil skeleton. This paper investigated the effect of leaching on the compressibility of Busan clay. The leached clay samples were obtained from the leaching procedure in laboratory with fresh water on the cell chamber. The initial salinity of about 17g/l in soil specimen, which was taken from Hwajeon industrial complex area, decreased to about 3g/l for 25 days. Compressible characteristics of the Busan leached clay were evaluated using the constant rate of strain test (CRS test), in which two kinds of strain rate, sec /%10 3−= ε & and sec /%10 4−= ε & , were adopted. Mechanical characteristics and physical properties between natural clay and leached clay were compared on the samples with the same conditions except salinity. The experimental test results of CRS tests showed that the compressibility of Busan leached clay increased as its salinity decreased. However, the void ratio, liquid limit, preconsolidation pressure and hydraulic conductivity of the leached sample decreased than these of the unleached clay due to leaching.